Glass frit and method of making glass frit

By heating the glass frit containing lithium, elements M, phosphorus, oxygen, boron and silicon at a lower temperature, forming crystallized glass with high ion conductivity, solving the problems of the existing oxide-based solid electrolyte in lithium ion conductivity and sintering temperature, and achieving efficient ion conductivity improvement at a lower temperature.

CN119923374APending Publication Date: 2025-05-02AGC INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380066941.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-20
Filing Date
2023-09-08
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The conventional oxide-based solid electrolyte has problems in lithium ion conductivity, and it is difficult to fully co-sinter the active substance and the solid electrolyte at a lower temperature, which affects the ion conductivity.

Method used

A glass frit containing lithium, elements M, phosphorus, oxygen, boron and silicon is provided, which is fluidized and crystallized by heating at a lower temperature to form a crystallized glass with high ion conductivity.

Benefits of technology

The full combination of the active substance and the solid electrolyte is achieved at a lower treatment temperature, which significantly improves the ion conductivity of the sintered body and avoids the problem of thermal damage to the active substance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119923374A_ABST
    Figure CN119923374A_ABST
Patent Text Reader

Abstract

A glass frit having lithium (Li), an element M, phosphorus (P), and oxygen (O), and having at least one of boron (B) and silicon (Si), the element M including at least one selected from the group consisting of zirconium (Zr), hafnium (Hf), tin (Sn), samarium (Sm), niobium (Nb), tantalum (Ta), tungsten (W), and molybdenum (Mo), the glass frit containing a seed crystal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to glass frit and a method of making glass frit. Background Art

[0002] In recent years, all-solid-state lithium-ion batteries have attracted considerable attention from the perspectives of safety and high-speed charging. Since all-solid-state lithium-ion batteries use solid electrolytes instead of liquid electrolytes, they are free from leakage and other issues, offering a high level of safety.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2021 / 039834 Summary of the Invention

[0006] Sulfide-based solid electrolytes are currently known as solid electrolytes for lithium-ion batteries. However, these solid electrolytes have the problem of generating hydrogen sulfide when reacting with moisture in the atmosphere.

[0007] On the other hand, oxide-based solid electrolytes have higher environmental stability and are easier to handle than sulfide-based solid electrolytes, and therefore are considered promising materials for solid electrolytes for all-solid-state batteries.

[0008] However, current oxide-based solid electrolytes have problems with lithium-ion conductivity. For example, the lithium-ion conductivity of current oxide-based solid electrolytes is more than an order of magnitude lower than that of typical sulfide-based solid electrolytes.

[0009] Against this background, LiTa2PO8 has attracted much attention in recent years as a new ion-conducting oxide with high ion conductivity (Patent Document 1).

[0010] However, the inventors of this application have learned that when using LiTa2PO8 crystals as the solid electrolyte in the electrode, it is not easy to fully co-sinter the active material and the solid electrolyte. If the active material and the solid electrolyte cannot be fully sintered, there is a problem that the contact area between the two is reduced, making it difficult to improve the ionic conductivity. On the other hand, if the sintering temperature is increased to fully achieve co-sintering, the active material may be damaged by heat, and its properties may not be fully exerted.

[0011] The present invention has been made in view of this background, and an object of the present invention is to provide a glass frit for a solid electrolyte that can fully bond an active material to a solid electrolyte even at a relatively low processing temperature. Another object of the present invention is to provide a method for producing such a glass frit.

[0012] The present invention provides a glass frit comprising lithium (Li), element M, phosphorus (P) and oxygen (O).

[0013] and having at least one of boron (B) and silicon (Si),

[0014] The element M includes at least one selected from zirconium (Zr), hafnium (Hf), tin (Sn), samarium (Sm), niobium (Nb), tantalum (Ta), tungsten (W), and molybdenum (Mo).

[0015] The glass frit contains seed crystals.

[0016] In addition, the present invention provides a method for manufacturing glass frit, comprising the following steps:

[0017] (1) a step of mixing raw materials containing lithium (Li), an element M, phosphorus (P), and oxygen (O), and containing at least one selected from boron (B) and silicon (Si), to prepare a mixed powder, wherein the element M contains at least one selected from zirconium (Zr), hafnium (Hf), tin (Sn), samarium (Sm), niobium (Nb), tantalum (Ta), tungsten (W), and molybdenum (Mo);

[0018] (2) heating the mixed powder to a temperature of 1200° C. to 1650° C. to obtain a melt,

[0019] (3) cooling the melt to form glass chips containing seed crystals, and

[0020] (4) A step of pulverizing the glass chips to obtain glass frit.

[0021] The present invention can provide a glass frit for a solid electrolyte that can sufficiently bond an active material to a solid electrolyte even at a relatively low treatment temperature. Furthermore, the present invention can provide a method for producing such a glass frit. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a flowchart schematically showing an example of a method for producing a glass frit according to one embodiment of the present invention.

[0023] Figure 2 This is a diagram showing an example of the particle size distribution of the glass frit (sample 2) according to one embodiment of the present invention.

[0024] Figure 3 This is a diagram showing an example of an X-ray diffraction pattern of a glass frit (sample 1) according to one embodiment of the present invention.

[0025] Figure 4 This is a diagram showing an example of an X-ray diffraction pattern of a glass frit (sample 2) according to another embodiment of the present invention.

[0026] Figure 5 This is a diagram showing an example of an X-ray diffraction pattern of a glass frit (sample 3) according to still another embodiment of the present invention.

[0027] Figure 6 This is a diagram showing an example of an X-ray diffraction pattern of a glass frit (sample 21) according to a comparative example. DETAILED DESCRIPTION

[0028] (Glass frit according to one embodiment of the present invention)

[0029] An embodiment of the present invention will be described below.

[0030] In one embodiment of the present invention, a glass frit is provided, comprising lithium (Li), element M, phosphorus (P), and oxygen (O).

[0031] and having at least one of boron (B) and silicon (Si),

[0032] The element M includes at least one selected from zirconium (Zr), hafnium (Hf), tin (Sn), samarium (Sm), niobium (Nb), tantalum (Ta), tungsten (W), and molybdenum (Mo).

[0033] The glass frit contains seed crystals.

[0034] As described above, the inventors of this application have learned that when using LiTa2PO8 crystals as the solid electrolyte in the electrode, it is not easy to fully co-sinter the active material and the solid electrolyte. If the active material and the solid electrolyte cannot be fully sintered, there is a problem that the contact area between the two becomes small, making it difficult to improve the ionic conductivity. On the other hand, if the sintering temperature is increased to fully achieve co-sintering, the active material may be damaged by heat, and its properties may not be fully exerted.

[0035] To this end, in one embodiment of the present invention, a glass frit including a seed crystal is provided.

[0036] The glass frit according to one embodiment of the present invention crystallizes to form crystallized glass when heated to a temperature above the crystallization temperature because it contains seed crystals containing element M. In addition, the glass frit according to one embodiment of the present invention fluidizes by heating at a relatively low temperature.

[0037] Therefore, when the glass frit according to one embodiment of the present invention is heat-treated together with an electrode active material, the glass frit according to one embodiment of the present invention crystallizes while being diffused around the electrode active material. This ensures a large contact area between the crystallized glass and the electrode active material, and as a result, significantly improves the ionic conductivity of the sintered body.

[0038] Furthermore, when the glass frit according to one embodiment of the present invention is used, a relatively low heat treatment temperature (for example, 700° C. to 1030° C.) can be employed, and thus a sintered body can be obtained without deteriorating the electrode active material.

[0039] (Characteristics of Glass Frit According to One Embodiment of the Present Invention)

[0040] Several features of a glass frit according to one embodiment of the present invention (hereinafter referred to as “first glass frit”) will be described below.

[0041] (composition)

[0042] The first glass frit contains Li, the element M, P, and O. Furthermore, the first glass frit contains at least one of B and silicon Si. In this application, Li, the element M, P, and O are collectively referred to as the "first component," and B and Si are collectively referred to as the "second component."

[0043] The "first component" primarily participates in crystallization when the first glass frit is heated to form crystallized glass, while the "second component" primarily participates in forming the glass matrix when the first glass frit is heated. However, it should be noted that these divisions are for ease of understanding and are not absolute. For example, Li, P, and O can be present in both the "first component" and the "second component."

[0044] As described above, the first glass frit contains the element M, and the element M may include at least one selected from the group consisting of Zr, Hf, Sn, Sm, Nb, Ta, W, and Mo. In particular, the element M preferably includes Ta.

[0045] The Li content is preferably in the range of 29.0 atomic % to 44.5 atomic % relative to the total amount of cations contained in the first glass frit, more preferably in the range of 29.5 atomic % to 42.0 atomic %, further preferably in the range of 30.0 atomic % to 39.0 atomic %, particularly preferably in the range of 30.5 atomic % to 36.0 atomic %, and most preferably in the range of 31.0 atomic % to 33.0 atomic %.

[0046] Furthermore, the content of the element M relative to the total amount of cations contained in the first glass frit is preferably 25.5 atomic % to 45.0 atomic %, more preferably 30.0 atomic % to 44.0 atomic %, further preferably 35.0 atomic % to 43.0 atomic %, particularly preferably 38.0 atomic % to 42.0 atomic %, and most preferably 40.0 atomic % to 41.0 atomic %.

[0047] The P content relative to the total amount of cations contained in the first glass frit is preferably 13.0 to 22.5 atomic %, more preferably 15.0 to 22.0 atomic %, further preferably 17.0 to 21.5 atomic %, particularly preferably 19.0 to 21.0 atomic %, and most preferably 20.0 to 20.5 atomic %.

[0048] When B is contained, the content of B is preferably 2.5 atomic % to 13.0 atomic % relative to the total amount of cations contained in the first glass frit, more preferably 3.0 atomic % to 11.0 atomic % , further preferably 3.5 atomic % to 9.0 atomic %, particularly preferably 4.0 atomic % to 7.0 atomic %, and most preferably 4.5 atomic % to 5.5 atomic %.

[0049] Furthermore, when Si is contained, the content of Si is preferably 0.8 atomic % to 3.8 atomic % relative to the total amount of cations contained in the first glass frit, more preferably 1.0 atomic % to 3.0 atomic %, further preferably 1.2 atomic % to 2.5 atomic %, particularly preferably 1.3 atomic % to 2.0 atomic %, and most preferably 1.4 atomic % to 1.7 atomic %.

[0050] The first glass frit may have a glass transition temperature Tg in the range of 600°C to 800°C.

[0051] In addition, in the first glass frit, the seed crystal may contain Ta2O x Crystal (x = 3 to 5). x≠5 indicates a state in which tantalum oxide crystals with Ta oxidation numbers of +2, +3, and +4 coexist in Ta2O5 crystals.

[0052] In addition, in the first glass frit, when the volume-based 50% particle size in the cumulative particle size distribution is defined as D50, the above-mentioned D50 is, for example, preferably in the range of 0.01 μm to 20 μm, more preferably in the range of 0.05 μm to 15 μm, further preferably in the range of 0.1 μm to 10 μm, particularly preferably in the range of 0.3 μm to 5 μm, and most preferably in the range of 0.5 μm to 3 μm.

[0053] When the first glass frit is used, it is heated to a temperature equal to or higher than the crystallization temperature.

[0054] Through this heating treatment, the seed crystals contained in the glass frit become nuclei, causing crystallization to proceed within the glass frit. As a result, crystallized glass is formed, consisting of a crystalline portion and surrounding grain boundaries. The primary crystalline portion is LiTa2PO8 when M=Ta, but other crystals may also be present.

[0055] The crystallized glass formed from the first glass frit has a characteristic of high ion conductivity. The ion conductivity of the crystallized glass is, for example, 0.40 mS / cm or higher.

[0056] The crystallized glass thus obtained also has the characteristic of containing a second component within the crystal. For example, when the first glass frit contains Si and B, Si and B are present within the crystals of the crystallized glass. Assuming M = Ta, the main crystal portion is a portion of the P in LiTa2PO8 substituted with at least one of Si and B, but other crystals may also be present.

[0057] (Method for Manufacturing Glass Frit According to One Embodiment of the Present Invention)

[0058] Next, refer to Figure 1 An example of a method for producing a glass frit according to an embodiment of the present invention having the above-described characteristics will be described.

[0059] Figure 1 An example of the flow of a method for producing glass frit according to one embodiment of the present invention is briefly shown in FIG.

[0060] like Figure 1 As shown, a method for producing glass frit according to one embodiment of the present invention (hereinafter referred to as “first method”) includes the following steps:

[0061] (1) a step of mixing raw materials containing Li, element M, P, and O and containing at least one selected from B and Si to prepare a mixed powder (S110),

[0062] (2) heating the mixed powder to a temperature of 1200° C. to 1650° C. to obtain a melt ( S120 ),

[0063] (3) a step of cooling the melt to form glass chips containing seed crystals (S130),

[0064] (4) A step of crushing the glass chips to obtain glass frit (S140).

[0065] Hereinafter, each step will be described in more detail.

[0066] (Step S110)

[0067] First, raw materials are mixed to prepare a mixed powder.

[0068] The raw materials include the first raw material for the aforementioned "first component" and the second raw material for the aforementioned "second component."

[0069] The first raw material and the second raw material are preferably mixed in a powder state.

[0070] The first raw material contains Li, element M, O, and P. As described above, element M represents at least one element selected from the group consisting of Zr, Hf, Sn, Sm, Nb, Ta, W, and Mo.

[0071] For example, the first raw material may include a compound and / or phosphate of Li. Alternatively, the first raw material may include a compound and / or phosphate of element M. For example, when element M is Ta, the first raw material may include tantalum oxide.

[0072] On the other hand, the second raw material contains Si and B. The second raw material may further contain Li and / or P. For example, the second raw material may contain Si compounds, lithium salts of silicon oxide, silicon phosphates, B oxides, lithium salts of boron oxide, and the like.

[0073] Furthermore, the first raw material and the second raw material may be composite oxides thereof.

[0074] Specifically, the following raw materials can be mentioned:

[0075] Li compounds are lithium carbonate (Li2CO3), lithium hydroxide and its hydrates (LiOH, LiOH.H2O), lithium oxide (Li2O), lithium sulfate (Li2SO4), lithium nitrate (LiNO3), lithium halides (LiF, LiCl, LiBr, LiI), lithium cyanide (LiCN), lithium citrate (Li3C6H5O7), lithium acetate (C2H3LiO2) and lithium oxalate (C2Li2O4);

[0076] When M=Ta is assumed, the compounds of element M are tantalum oxide (Ta2O5, TaO2), tantalum halide (TaF5, TaCl5, Ta2Br 10 、Ta2I 10 ), tantalum oxide fluoride (TaFO2);

[0077] Phosphoric acid is H3PO4, H4P2O7, HPO3, P2O5;

[0078] Boric acid is H3BO3, HBO2, H2B4O7;

[0079] The compound of Si is silicon dioxide (SiO2);

[0080] The composite oxides are lithium phosphate (LiPO3, Li3PO4, LiH2PO4), lithium silicate (Li2SiO3, Li4SiO4), lithium borate (LiBO2, Li3BO3, Li2B4O7), and lithium tantalate (LiTaO3).

[0081] The first raw material and the second raw material are thoroughly mixed to prepare a mixed powder.

[0082] (Step S120)

[0083] Next, the prepared mixed powder is heated and melted in the air to form a melt.

[0084] The melting temperature is in the range of 1200°C to 1650°C, preferably in the range of 1300°C to 1600°C, and more preferably in the range of 1400°C to 1500°C.

[0085] The melting time varies depending on the amount of the mixed powder and the melting temperature, and may be, for example, 5 hours or less. The melting time may be, for example, 2 hours or less, 1 hour or less, or 30 minutes or less. The heating and melting atmosphere is preferably air, but may also be an oxidizing atmosphere or an inert gas atmosphere.

[0086] (Step S130)

[0087] The melt is then cooled.

[0088] The cooling method is not particularly limited. The crystallization process from the melt follows a two-stage process of nucleation and crystal growth from the nucleus. Even if a seed crystal is included to form a nucleus, glass can be obtained by cooling faster than the growth rate of the crystal. For example, the melt can be rapidly cooled by a roll-out machine, a press, or by dropping into a cooling liquid.

[0089] The melt is cooled to form glass chips containing seed crystals. In this case, the seed crystals serving as nuclei may be contained in the melt or the nuclei may be generated from the melt.

[0090] The seed crystal contains an oxide of element M. For example, when element M is Ta, the seed crystal can be Ta2O x (x=3~5).

[0091] (Step S140)

[0092] Next, the obtained glass chips are pulverized to form glass frit. The method for pulverizing the glass chips is not particularly limited, and a conventional method such as a dry ball mill method can be used.

[0093] When the volume-based 50% particle size in the cumulative particle size distribution is defined as D50, the glass frit is preferably pulverized until D50 falls within a range of 0.01 μm to 20 μm.

[0094] Through the above steps, the glass frit according to one embodiment of the present invention can be produced.

[0095] The glass frit produced by the first method is heated to a temperature equal to or higher than the crystallization temperature before use. The heat treatment temperature may be, for example, in the range of 700°C to 1030°C.

[0096] By such a heat treatment, the seed crystals contained in the glass frit become nuclei, and crystallization proceeds within the glass frit, resulting in the formation of crystallized glass having a crystal portion and a surrounding grain boundary portion.

[0097] The formed crystallized glass has high ionic conductivity. For example, the crystallized glass may have an ionic conductivity greater than 0.40 mS / cm.

[0098] Example

[0099] The following describes examples of the present invention. Note that in the following description, Examples 1 to 4 and 11 to 13 are examples, and Examples 21 to 23 are comparative examples.

[0100] (Example 1)

[0101] Glass frit was prepared by the following method.

[0102] (Production of glass scraps)

[0103] First, 24.11 g of tantalum oxide (Ta2O5, manufactured by Kanto Chemical, 3N5 high-purity reagent) powder, 4.69 g of lithium metaphosphate (LiPO3, manufactured by Hakushin Chemical Research Institute), 0.67 g of lithium metaborate (LiBO2, manufactured by Fujifilm Wako Chemicals, purity 99% or greater), 0.40 g of lithium carbonate (Li2CO3, manufactured by Kanto Chemical, 3N5 high-purity reagent), and 0.37 g of lithium metasilicate (Li2SiO3, manufactured by Strem Chemicals, purity 99%) were mixed to prepare a mixed powder. The mixed powder was prepared so that, in terms of cation atomic percent, lithium (Li) was 32.4%, tantalum (Ta) was 40.7%, phosphorus (P) was 20.3%, silicon (Si) was 1.5%, and boron (B) was 5.0%.

[0104] Next, 30 g of the mixed powder was placed in a platinum container and heated in air to melt. The melting temperature was 1450° C. and the melting time was 30 minutes. The melt was then stirred thoroughly with a platinum rod.

[0105] Next, the obtained melt was rapidly cooled using a rolling mill, thereby obtaining approximately 27 g of flaky glass chips (hereinafter referred to as "glass chips 1").

[0106] It was confirmed that the obtained glass chips 1 contained a mixture of a turbid portion and a transparent portion.

[0107] (Production of glass frit)

[0108] Next, the glass cullets 1 were pulverized as follows to prepare glass frit.

[0109] 15 g of glass chips 1 and 250 g of stabilized zirconia balls with a diameter of 10 mm were placed in a 250 mL HDPE container and pulverized in a ball mill at a rotation speed of 94 rpm for 15 hours.

[0110] In this manner, a white powdery glass frit (hereinafter referred to as "Sample 1") was obtained.

[0111] (Example 2)

[0112] A glass frit (hereinafter referred to as "sample 2") was prepared by the same method as in Example 1 described above.

[0113] In Example 2, in the above-mentioned step (preparation of glass flakes), the powders were mixed to prepare a mixed powder such that, on a cation atomic % basis, the contents of Li were 34.0%, Ta were 38.8%, P were 19.4%, Si were 1.8%, and B were 6.1%. Other conditions were the same as those in Example 1.

[0114] (Example 3)

[0115] Glass frit (hereinafter referred to as "Sample 3") was prepared by the same method as in Example 1 described above.

[0116] In Example 3, in the above-mentioned step (preparation of glass flakes), the powders were mixed to prepare a mixed powder such that, on a cation atomic % basis, the contents of Li were 36.7%, Ta were 35.4%, P were 17.7%, Si were 2.4%, and B were 7.9%. Other conditions were the same as those in Example 1.

[0117] (Example 4)

[0118] Glass frit (hereinafter referred to as "Sample 4") was prepared by the same method as in Example 1 described above.

[0119] In Example 4, in the above-mentioned step (preparation of glass flakes), the powders were mixed to prepare a mixed powder such that, on a cation atomic % basis, Li was 40.1%, Ta was 31.0%, P was 15.5%, Si was 3.1%, and B was 10.3%. Other conditions were the same as those in Example 1.

[0120] (Example 11)

[0121] Glass frit (hereinafter referred to as "Sample 11") was prepared by the same method as in Example 1 described above.

[0122] In Example 11, the melting temperature of the mixed powder was set to 1300° C. and the melting time was set to 60 minutes. Other conditions were the same as those in Example 1.

[0123] (Example 12)

[0124] Glass frit (hereinafter referred to as "Sample 12") was prepared by the same method as in Example 1 described above.

[0125] In Example 12, the melting temperature of the mixed powder was set to 1550° C. and the melting time was set to 20 minutes. Other conditions were the same as those in Example 1.

[0126] (Example 13)

[0127] Glass cullets (hereinafter referred to as "glass cullets 13") were prepared by the same method as in Example 1. Furthermore, the glass cullets 13 were pulverized to prepare glass frit (hereinafter referred to as "sample 13").

[0128] In Example 13, the time for the pulverization treatment of the glass frit 13 was set to 6 hours. The other conditions were the same as those in Example 1.

[0129] (Example 21)

[0130] Glass frit (hereinafter referred to as "Sample 21") was prepared by the same method as in Example 1 described above.

[0131] In Example 21, in the above-described step (Production of Glass Cuttings), the powders were mixed to prepare a mixed powder such that, on a cation atomic % basis, the contents of Li were 44.6%, Ta were 25.4%, P were 12.7%, Si were 4.0%, and B were 13.3%. Other conditions were the same as those in Example 1.

[0132] (Example 22)

[0133] An attempt was made to produce glass chips (hereinafter referred to as "Sample 22") by the same method as in Example 1.

[0134] In Example 22, the melting temperature of the mixed powder was set to 1100° C., and the melting time was set to 100 minutes.

[0135] However, the mixed powder cannot be fully melted under these melting treatment conditions.

[0136] (Example 23)

[0137] The mixture was prepared by the following method.

[0138] First, 23.45 g of lithium metaphosphate (LiPO3, manufactured by Hakushin Chemical Research Institute), 3.35 g of lithium metaborate (LiBO2, manufactured by Fujifilm Wako Chemicals, purity 99% or higher), 2.00 g of lithium carbonate (Li2CO3, manufactured by Kanto Chemical, 3N5 high-purity reagent), and 1.85 g of lithium metasilicate (Li2SiO3, manufactured by Strem Chemicals, purity 99%) were mixed to prepare a mixed powder. The mixed powder was prepared so that, in terms of cation atomic percentage, lithium (Li) was 54.7%, phosphorus (P) was 34.3%, silicon (Si) was 2.5%, and boron (B) was 8.5%.

[0139] Next, the mixed powder was placed in a platinum container and melted by heating at a temperature of 1300°C for 30 minutes. The melt was then thoroughly stirred with a platinum rod.

[0140] Next, the obtained melt was rapidly cooled using a rolling mill, thereby obtaining flake-shaped glass chips (hereinafter referred to as "glass chips 23").

[0141] Next, 12.28 g of tantalum oxide (Ta₂O₅, manufactured by Kanto Chemical, 3N5 high-purity reagent) powder was added to 3.00 g of glass shavings 23. 250 g of stabilized zirconia balls with a diameter of 10 mm were added to this mixed powder. The mixture was placed in a 250 mL HDPE container and pulverized in a ball mill. The rotation speed was 94 rpm, and the pulverization time was 15 hours.

[0142] Thus, a white powder was obtained (hereinafter referred to as "Sample 23").

[0143] Table 1 below collectively shows the manufacturing conditions and the like of the samples manufactured in each example.

[0144] [Table 1]

[0145]

[0146] (evaluate)

[0147] The following evaluations were performed using each sample.

[0148] (Measurement of glass transition temperature Tg)

[0149] The glass transition temperature Tg of each sample was measured by TG-DTA (thermogravimetric-differential thermal analysis). The measurement was performed in air by heating from room temperature to 1000°C at a rate of 5°C per minute.

[0150] (Particle size distribution measurement)

[0151] The particle size distribution of each sample was measured using a laser diffraction scattering device (SALD-2100, manufactured by Shimadzu Corporation), and D50 (50% particle size based on volume in the cumulative particle size distribution) was determined from the obtained results.

[0152] Figure 2 ] An example of the particle size distribution measurement results obtained for Sample 2 is shown in FIG. D50 of Sample 2 is 1.5 μm.

[0153] (X-ray diffraction analysis)

[0154] Each sample was subjected to X-ray diffraction analysis (Cu-Kα ray), and based on the obtained results, it was evaluated whether the sample contained seed crystals.

[0155] Figures 3 to 6 An example of the obtained X-ray diffraction pattern is shown in FIG. Figure 3 The X-ray diffraction pattern obtained in Sample 1 is shown in FIG. Figure 4 The X-ray diffraction pattern obtained in Sample 2 is shown in FIG. Figure 5 The X-ray diffraction pattern obtained in Sample 3 is shown in FIG. Figure 6 The X-ray diffraction pattern obtained in Sample 21 is shown in FIG.

[0156] according to Figures 3 to 5 Diffraction peaks derived from crystals were observed in Samples 1 to 3, indicating that seed crystals were present in Samples 1 to 3. These diffraction peaks correspond to tantalum oxide (Ta2O5).

[0157] On the other hand, no peak corresponding to crystals was observed in Sample 21, indicating that Sample 21 was amorphous.

[0158] (Determination of ionic conductivity)

[0159] Crystallized glass was prepared from each sample by the following method, and ion conductivity was measured using the obtained crystallized glass.

[0160] (Production of Crystallized Glass)

[0161] First, each sample was molded to produce a molded body.

[0162] 0.5 g of glass frit (sample) was placed in a superhard mold having a diameter of 10 mm, and uniaxial pressing was performed at a pressing pressure of 40 MPa for 2 minutes.

[0163] Thereafter, isostatic pressing was further performed at a pressure of 200 MPa to obtain a molded body having a diameter of 10 mm and a thickness of 1.5 mm.

[0164] Next, the molded body was heat-treated by the following method.

[0165] First, the molded body was placed on a platinum dish. The dish was heated to 950°C in the atmosphere at a heating rate of 300°C / hour. After being kept at 950°C for 5 hours, the dish was cooled to room temperature at a cooling rate of 300°C / hour.

[0166] After the heat treatment, a white crystallized glass (hereinafter referred to as a "crystallized glass sample") was obtained. The size of the crystallized glass sample was 9.0 mm in diameter and 1.3 mm in thickness.

[0167] (AC impedance measurement)

[0168] Gold electrodes (5 mm in diameter) were formed on both sides of the crystallized glass sample by vapor deposition. Next, a measurement voltage of 20 mV was applied to the gold electrodes, and the impedance of the glass piece was measured by AC impedance spectroscopy. The measurement was performed using a 4990EDMS-120K (manufactured by TOYO Corporation) at a measurement frequency of 100 Hz to 100 MHz. The impedance spectrum obtained was fitted with an equivalent circuit using ZView, the equivalent circuit analysis software included with the device, to evaluate the ionic conductivity of lithium ions.

[0169] The evaluation results obtained for each sample are collectively shown in Table 2 below.

[0170] [Table 2]

[0171]

[0172] As shown in Table 2, it is found that sample 21 and sample 23 do not contain seed crystals. On the other hand, it is found that samples 1 to 4 and samples 11 to 13 contain Ta2O5 seed crystals.

[0173] As shown in Table 2, the crystallized glasses produced from Samples 21 and 23 exhibited relatively poor ion conductivity. In contrast, the crystallized glasses produced from Samples 1 to 4 and 11 to 13 exhibited high ion conductivity exceeding 0.40 mS / cm.

[0174] Based on the above results, when Sample 1 (or any one of Samples 2 to 4 and Samples 11 to 13, and the same applies hereinafter) is added to an electrode active material and heated, it is predicted that Sample 1 will flow and diffuse around the electrode active material, and that Sample 1 will become crystallized glass. Therefore, it is predicted that the resulting sintered body will have a large contact area between the crystallized glass and the electrode active material and high ion conductivity.

[0175] The present invention has the following aspects.

[0176] (Method 1)

[0177] A glass frit having lithium (Li), element M, phosphorus (P) and oxygen (O),

[0178] and having at least one of boron (B) and silicon (Si),

[0179] The element M includes at least one selected from zirconium (Zr), hafnium (Hf), tin (Sn), samarium (Sm), niobium (Nb), tantalum (Ta), tungsten (W), and molybdenum (Mo).

[0180] The glass frit contains seed crystals.

[0181] (Method 2)

[0182] The glass frit according to aspect 1, wherein the element M is Ta.

[0183] (Method 3)

[0184] The glass frit according to aspect 1 or 2 has a glass transition temperature Tg in the range of 600°C to 800°C.

[0185] (Method 4)

[0186] The glass frit according to any one of aspects 1 to 3, wherein the seed crystal contains Ta2O x (x=3~5) crystal.

[0187] (Method 5)

[0188] The glass frit according to any one of aspects 1 to 4, wherein, when a volume-based 50% particle size in a cumulative particle size distribution is defined as D50,

[0189] The above-mentioned D50 is in the range of 0.01 μm to 20 μm.

[0190] (Method 6)

[0191] A method for manufacturing glass frit, comprising the following steps:

[0192] (1) Raw materials containing lithium (Li), an element M, phosphorus (P), and oxygen (O), and containing at least one selected from boron (B) and silicon (Si), are mixed to prepare a mixed powder, wherein the element M contains at least one selected from zirconium (Zr), hafnium (Hf), tin (Sn), samarium (Sm), niobium (Nb), tantalum (Ta), tungsten (W), and molybdenum (Mo);

[0193] (2) heating the mixed powder to a temperature of 1200° C. to 1650° C. to obtain a melt;

[0194] (3) cooling the melt to form glass chips containing seed crystals,

[0195] (4) The glass chips are crushed to obtain glass frit.

[0196] This application claims priority based on Japanese Patent Application No. 2022-148695, filed on September 20, 2022, the entire contents of which are incorporated herein by reference.

Claims

1. A glass frit comprising lithium (Li), an element M, phosphorus (P) and oxygen (O), and at least one of boron (B) and silicon (Si), The element M includes at least one selected from zirconium (Zr), hafnium (Hf), tin (Sn), samarium (Sm), niobium (Nb), tantalum (Ta), tungsten (W) and molybdenum (Mo), The glass frit includes seed crystals.

2. The glass frit according to claim 1, wherein: The element M is tantalum (Ta). 3 . The glass frit according to claim 1 , which has a glass transition temperature Tg in the range of 600° C. to 800° C.

4. The glass frit according to claim 1 or 2, wherein: The seed crystal contains Ta2O x Crystal, x=3~5.

5. The glass frit according to claim 1 or 2, wherein: When the volume-based 50% particle size in the cumulative particle size distribution is defined as D50, The D50 is in the range of 0.01 μm to 20 μm.

6. A method for manufacturing glass frit, comprising the following steps: (1) raw materials containing lithium (Li), an element M, phosphorus (P), and oxygen (O) and containing at least one selected from boron (B) and silicon (Si) are mixed to prepare a mixed powder, wherein the element M contains at least one selected from zirconium (Zr), hafnium (Hf), tin (Sn), samarium (Sm), niobium (Nb), tantalum (Ta), tungsten (W), and molybdenum (Mo); (2) heating the mixed powder to a temperature of 1200° C. to 1650° C. to obtain a melt; (3) cooling the melt to form glass scraps containing seed crystals, (4) The glass scraps are crushed to obtain glass frits.